‘Telling Tales’. An investigation into the representation of disability in classic children’s fairy tales - Alan Hodkinson; Jemma Park (Educational Futures, 2017)
The research examined the cultural construction of disability found within children’s traditional fairy tales that are employed to support the English National Curriculum. The study employed proto text analysis, a meta-analysis process which combines textual analysis, critical discourse analysis and semiotics, to uncover the hidden representations and stereotypes relating to disability that were contained within well-known children’s fairy tales. The study, which examined five story books in detail, found consistent themes which included normalcy, the emphasis on the ‘perfect’ physical appearance, exclusion, avoidance and portrayal of the disabled character as an ‘object of evil’ as well as the employment of the ‘happily ever after’ story ending. The research concludes these children’s fiction books, commonly employed to support the English National Curriculum, are problematic in terms of how they represent disability. The authors argue that this form of children’s literature is introducing young children to ableist assumptions and oppressive attitudes towards disability which we suggest could be a factor in why these attitudes are replicated within society.